Killing moon ebook - Nesbo, Jo (Harry Hole, 2023)
NEW YORK TIMES BEST SELLER • This killer will get inside your head. • Brilliant rogue police investigator Harry Hole is back, this time as an outsider assembling his own team to help find a serial killer who is murdering young women in Oslo in the next novel in the internationally best-selling series. "One of today's most interesting thriller writers." —Lee Child, author of the #1 best-selling Jack Reacher series THE HUNT IS ON AND THE POLICE ARE RUNNING OUT OF TIME. Two young women are missing, their only connection a party they both attended, hosted by a notorious real-estate magnate. When one of the women is found murdered, the police discover an unusual signature left by the killer, giving them reason to suspect he will strike again. THEY'RE FACING A KILLER UNLIKE ANY OTHER. And exposing him calls for a detective like no other. But the legendary Harry Hole is gone—fired from the force, drinking himself to oblivion in Los Angeles. It seems that nothing can entice him back to Oslo. Until the woman who saved Harry's life is put in grave danger, and he has no choice but to return to the city that haunts him and track down the murderer. CATCHING HIM WILL PUSH HARRY TO THE LIMIT. He'll need to bring together a misfit team of former operatives to accomplish what he can't do alone: stop an unstoppable killer. But as the evidence mounts, it becomes clear that there is more to this case than meets the eye...